ADAPTATION ACTIONS OF RICE HARVESTING LABORS TOWARD THE IMPACT OF USING HARVESTER COMBINE MACHINE (HCM) IN DURIAN SEGINIM VILLAGE SOUTH BENGKULU REGENCY INDONESIA - Arianti, Nyayu Neti; Priyono, Basuki Sigit; Reswita, Reswita (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2024)
Agricultural mechanization used provides benefits in farming, namely cost efficiency. Harvester Combine Machine (HCM) use in rice farming can eliminate harvesting labor. Therefore, this study aims to analyze the impact of HCM use to the rice farming laborers in Durian Seginim Village, and to analyze the adaptation actions taken by the laborers because of the impact of using HCM. The research was conducted in October 2022. The number of respondents was 100 and the data was taken randomly from 192 rice farmers who use HCM. The data analysis method used is descriptive qualitative analysis. The results showed that the use of HCM in rice farming provides benefits for farm owners in savings in harvesting costs of 23.99 percent. However, the use of HCM reduced employment opportunities by 58.72- time allocation of labor/Ha (36.78% of the total farming workforce). Specifically for harvesting workers, labor absorption decreased by 42.70 time allocation of labor/Ha (25.91%) which was dominated by female workers from outside the family. Female workers experienced a decline in their income and contribution to household income by 46.99 percent. The three adaptation actions most frequently carried out by harvesting workers are working in the on-farm agricultural sector outside rice farming (21%), working on land that does not use HCM (17%), and selling large or small of rice stock, user savings, etc. (13%)